Exploring the potential development of tourism products: a case study at tumpat district - Adisak A/La Ran; Agalya A/P Ravimaran; Afikah Amira Ahmad; Ahmad Aiman Aqil Jamidin (2022)
The aim of this study is to investigate the potential development of tourism products in Tumpat District, a region with rich cultural heritage and natural resources. Tumpat District, located in the state of Kelantan, Malaysia, offers a diverse range of attractions including historical sites, traditional crafts, scenic landscapes, and religious landmarks. However, the district's tourism industry has yet to fully capitalize on these resources. This research approach to gather qualitative data. Interviews and focus group discussions are conducted with local stakeholders, including tourism authorities, community representatives, and industry professionals, to gain insights into their perspectives on potential tourism product development. Preliminary findings reveal that Tumpat District has untapped potential for tourism product diversification and enhancement. The existing attractions, such as Wat Photivihan Temple, Pantai Sri Tujuh, and the cultural village of Kampung Laut, are highly regarded by tourists. However, there is a need for infrastructure development, marketing strategies, and community involvement to fully harness the district's tourism potential. This study contributes to the existing literature on tourism product development by providing empirical evidence from a specific case study. The findings can guide policymakers, tourism authorities, and local communities in formulating effective strategies for product diversification, infrastructure improvement, and destination marketing. By developing new tourism products and improving existing ones, Tumpat District can attract a wider range of tourists, extend their length of stay, and boost the local economy. Keywords: tourism product development, Tumpat District, tourist preferences, stakeholder perspectives, destination marketing